2002
DOI: 10.1136/heart.88.5.521
|View full text |Cite
|
Sign up to set email alerts
|

Arterial endothelial function is impaired in treated depression

Abstract: Objectives: To determine whether patients with treated depression but no other risk factors for coronary heart disease (CHD) have abnormal arterial endothelial function, an abnormality that is common to other acquired risk factors for CHD. Design: Case-control study. Setting: Secondary care departments of cardiology and psychiatry in a single centre and the surrounding community. Participants: Patients with treated depression and matched healthy controls, aged 18-55 years, without conventional acquired risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
96
3
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 21 publications
10
96
3
5
Order By: Relevance
“…For example, a previous study from our laboratory found that the olfactory bulbectomy rodent model of depression was associated with a generalized attenuation in sympathoexcitatory responses, but no specific change in the gain of the baroreflex (30). Similarly, Broadley et al (34) found no baroreflex sensitivity differences between normal control subjects and patients who met DSM-IV diagnostic criteria for depression. Also, Watkins et al (18) reported that symptoms of anxiety, but not symptoms of depression, were associated with reduced baroreflex sensitivity in a sample of patients following acute myocardial infarction, suggesting that anxiety may be a mediating factor in this group's previously reported cardiac changes associated with depression.…”
Section: Discussionmentioning
confidence: 91%
“…For example, a previous study from our laboratory found that the olfactory bulbectomy rodent model of depression was associated with a generalized attenuation in sympathoexcitatory responses, but no specific change in the gain of the baroreflex (30). Similarly, Broadley et al (34) found no baroreflex sensitivity differences between normal control subjects and patients who met DSM-IV diagnostic criteria for depression. Also, Watkins et al (18) reported that symptoms of anxiety, but not symptoms of depression, were associated with reduced baroreflex sensitivity in a sample of patients following acute myocardial infarction, suggesting that anxiety may be a mediating factor in this group's previously reported cardiac changes associated with depression.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, endothelial dysfunction occurs in the large arteries of untreated patients 10 and those taking antidepressant therapy. 11 Compared with matched participants without depression there is also a greater prevalence 12 and incidence 13 of increased carotid intima-media thickness and an increase in aortic pulse wave velocity, 14 even after adjustment for traditional risk factors. The studies to date, however, all pertain to large arteries, and, whereas endothelial dysfunction may be indicative of a proatherogenic state, this does not explain the development of microvascular pathology in the brain.…”
mentioning
confidence: 99%
“…Decreased cardiovascular fitness in males who enlisted for military service has been a predictive factor for future depression, thus the association between depression and CVD seems bidirectional 10 . Although the relationship between depression and CVD is unclear in terms of which one triggers another one, previous studies have shown that there is a close relationship between endothelial dysfunction, atherosclerosis, and depression [11][12][13] . Inflammation is another important entity in pathophysiology of cardiovascular disease and depression.…”
Section: Introductionmentioning
confidence: 99%